Guru Ideal menurtu Imam Ghozali dan Syekh Az-Zarnuji dalam Kitab Ta'limul Muta'aliim dan Ihya' Ulumuddin serta Kritik guru saat mengajar - Benny Mahendra (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2021)
This research was conducted by examining the books of Ta'limul Muta'aliim and Ihya 'Ulumuddin. The researcher discusses the ideal teacher according to Az-zarnuji and Al-Ghozali. Both were chosen because they have traditional educational thoughts but are still feasible to apply today. The main purpose of this study is to determine the ideal teacher in view of both, determine the ideal teacher standard in modern learning and criticize the teacher's condition when teaching. The initial stage of this research collected library data and literature texts related to education, especially the ideal teacher according to Az-Zarnuji and Al-Ghozali. The second stage examines the Teacher in both views and examines the historiography of the writing of the two books. The method used is descriptive qualitative method. This method is used to present the ideal teacher in the views of Az-Zarnuji and Al-Ghozali and to criticize the teacher's condition when teaching. Specific targets in this study are 1) Ideal Teacher according to Az-Zarnuji and Al-Ghozali by studying the books of Ihya 'Ulumuddin and Ta'liimul Muta'alim. 2) Identifying the factors that influence their thinking in education 3) Identifying criticisms and providing solutions related to teacher conditions while teaching. The findings include low teacher competence, Al-Ghazali and Az-Zarnuji's thinking is influenced by Sufism and Worship, The criticism that appears is that teachers do not understand the role of educators, Teaching Motivation is influenced by internal and external factors in the teacher's personality.